Prospect and Implementation of m-learning for Future Curriculum - Abdullah, Muhammad Ridhuan Tony Lim; Saedah Siraj, Saedah (2009)
Technology advancement has indeed revolutionized how we conduct our lives including education, but in so doing, technology creates a widening educational gap between privileged and underprivileged countries. While students in the first world countries fiddling with the state of the art computer engaging learning electronically, their counterparts in the third world countries are still struggling to learn with torn textbooks. However the latest advanced approach, mobile learning or m-learning does not have to face the same fate. This new wireless entry in learning aided by mobile technologies, m-learning, will lead to the emergence of new pedagogical approach which facilitates students-centered or self-access learning experience, thus increase opportunities to succeed in education anytime and anywhere, even despite their limitation of access to educational facilities and infrastructure. Thus the paper highlights the benefits and prospect of m-learning implementation for future curriculum to promote education for all by defining what m-learning is; probing into the prospect of m-learning and its benefit; and ending with a discussion of m-learning process in curriculum implementation before we conclude.